An interdisciplinary clinical discussion as an instrument for the formation of the therapist: an experience in phonoaudiology - Silveira Alves de Oliveira, Beatriz; Abbes Clapés Margall, Soraya (O Mundo da Saúde, 2006)
This text is based on the questions related to the formation of the therapist in the health field, articulating them with the teaching/learning process. The discussion is done on the light of a theoretical conception that values the interactive aspects of subjects, from a gaze that looks for her singularity. We argue, also, that interdisciplinarity as a factor essential for this formation of the therapist and we also report on these questions in Phonoaudiology. We finish the article discribing our experience of interdisciplinary clinical discussions in the Course of Phonoaudiology of the University Center São Camilo, as an example of a practice of the undergraduate level where all these questions present themselves.